Remote ischaemic conditioning: individual patient data meta-analysis of acute stroke trials and prospective MRI evaluation in healthy adults - Dhillon, Permesh Singh (2021)
Background: Remote ischaemic conditioning (RIC) is a promising neuroprotective method, with preclinical studies showing improved neurological outcome following acute stroke. However, early phase randomised controlled trials (RCTs) have given rise to conflicting results. Furthermore, the optimal strategy to apply RIC in humans is unknown. Clinical studies have utilised a variety of doses and methods, ranging from a single ‘dose’ using one limb, to daily application for 300 days using two limbs, decisions that are not based on meaningful pre-clinical data. A reliable way to directly measure end-organ effects of RIC would allow optimal methods of application and ‘dose’ to be determined, thereby informing clinical trial design.